Technical Efficiency of Giant African Land Snail (Archachatina marginata) Production in Plateau State, Nigeria - Zira, B.D.; Modu, M.; Mathew, D.E. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
The Low productivity in Non-timber Forest Product (NTFP) is mainly due to the inability of the farmers to exploit the available technologies fully, resulting in lower efficiencies of production. This study employed a Cobb-Douglas stochastic frontier production function to measure the level of technical efficiency and its determinants in Giant African land snail production in Plateau State, Nigeria. Primary data was generated through the use of closed and open ended structured questionnaire in line with the objectives of the study. Respondents were selected through a systematic random sampling procedure. Eighty-seven Giant African land snail farmers were selected, from whom socioeconomic and input-output data were obtained using the cost-route approach. The parameters of the stochastic frontier production function were estimated using the maximum likelihood method. The study revealed stock size (0.44), labour (0.55) and feed (0.15) were positively and significantly related to output at 5% level of significance. Socioeconomic factors influencing technical efficiency directly were farming experience and credit access at 5% level of significance. Age was negatively and significantly related to technical efficiency at 5% level of significance. Result of returns to scale analysis showed that snail production is at the stage of increasing returns to scale. The study recommend that Snail farmers should have greater access to formal credit facilities from lending institutions in order to expand and improve their production. They should be encouraged to form stronger co-operative societies so as to expandtheir scope of production and marketing. Farmers are advised to grow most of the green feed stuffs the snails eat to save costs.